The development of low cost sensor technology to provide augmented feedback for on-water rowing - Collins, D. J.; Anderson, R.; O'Keeffe, D. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
Investigations to identify ways to improve stroke technique of rowers are on going (Anderson et al 2005). However, the majority of these studies are laboratory based and thus neglect the effects of the oar and water have on the rowing stroke. Traditionally on-water testing has tended to concentrate on the forces produced by the rower at the oar handle, foot stretcher and on boat by the rower but not the actual rowing technique (Hill, 2001). The purpose of this study was to design and develop a system that would provide quantitative feedback of the rowers` technique on the water. This was accomplished through the integration of low cost electronic sensors, specific software interface and use of wireless technology (Anderson & Collins 2004).